Zero-waste in & out refocusing the mall as a circular economic space - Ong, Phoebe Gayle Y.; Sicam, Olivia Alma (Quezon City College of Architecture, University of the Philippines Diliman, 2022)
Because Filipinos are generally consumer-driven, commercial activity in the country has been drastically increasing, whether it be through online or physical transactions. This, then, sheds light to the underlying issue of an overwhelmed waste management system here in the country as the consumption of products immediately results in commercial waste. Despite the positive contribution this has to our economy, waste in general is inevitably produced excessively, which poses as a major issue concerning the country's overall carbon footprint as well as the continuous proliferation of a linear economic dynamic, i.e., the ongoing use of the 'take-make-consume-throw away' scheme in the production of commercial products.
Not only does this emphasize the "need" to recycle more than to reduce and reuse, but it also highlights the limitations of the government in addressing the general issue of waste mitigation as existing legislation merely dictates surface-level means for waste management, e.g., the mere provision of color-coded, segregated trash bins in all spaces. Considering this rule in the commercial setting, human engagement remains subpar and limited as these legal provisions have no profound impact in our overall consciousness for our retail purchase in every commercial establishment we go to.
With this, my project addresses the issue of a lack in a design-based approach in the implementation of waste mitigation and regulation measures in typical commercial spaces such as malls with special attention to the integration of community-engaging efforts in altering our perception and use for packaging in the commercial setting.
Specifically, my project will be looking into proposing an alternative design model for shopping malls in the country derived from the considerations needed to mitigate the following commercial wastes : plastics, electronics, food, and other organic wastes consumed within the mall premises. In addition, this model is integrated with a hub for packaging incubation and regulation. With the goal of mitigating the wastes, zero -waste systems are to be considered as the core design principle of this mall design model to make use of a circular economy. Alongside this, Extended Producer Responsibility (EPR) frameworks are also to be integrated in the mall operations to achieve the intended results in the overall waste regulated within the mall.
This proposal seeks the support of both the National and Local Government Units as well as the private sector in the design of future malls to be put up in the country. Also, this should immerse both existing zero-waste lifestyle users, those willing to give the said lifestyle a try, as well as all constituents from the National Capital Region (NCR), especially those inhabiting the City of Caloocan, to recognize proper waste management measures in the commercial and, hopefully, the individual and household level.
The introduction of this design model dedicated to the promotion and establishment of proper waste management consciousness and involvement in Filipinos should inevitably result in a more environmentally conscious demographic that celebrated lesser carbon footprint and a healthier relationship with both the built and unbuilt environment.
includes appendices.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Refuse and refuse disposal -- Caloocan City; Salvage (Waste, etc.) -- Caloocan City; Waste minimization -- Caloocan City